The prevalence of smoking and its impact on disability in multiple sclerosis - Tadić, Daliborka M; Đajić, Vlado; Grgić, Sanja; Miljković, Siniša (Scripta Medica, 2019)
Introduction: Etiology of multiple sclerosis (MS) involves multifactorial interactions among genetic and environmental factors. Cigarette smoking is one of the most important environmental factors that increase the disease risk by about 50%. The aim of the research to assess the prevalence of smoking in MS patients compared to the general population, and to assess the association between smoking and physical disability in MS patients. Materials and Methods: A cross-sectional study included 100 MS patients and 50 healthy people. For estimation of the degree of physical disability, the Expanded Disability Status Scale (EDSS) was used, and for clinical and demographic data we used a general questionnaire. In order to collect data on the smoking, the questionnaire for examining risk factors for vascular disease among patients with MS was used. Results: Analysis of smoking incidence showed that, between MS and control group, smoking had been a dependent variable (χ2 = 6.258, p = 0.04). In smokers, seen in both groups, there was no statistically significant difference in the number of cigarettes, nor in the duration of smoking. There was no significant correlation between smoking in MS group and the index of disease progression (r=0.216, p=0.133). Also, the relationship between EDSS and smoking had no statistical significance, as well as between the disease course and smoking (χ2 = 1.531, p = 0.216). Conclusion: In view of the relevance of smoking in MS, it is important to modify this environmental factor and thus prevent its effect on the onset and progression of MS. Keywords: multiple sclerosis, smoking